Spontaneous rupture of a renal angiomyolipoma at 25 weeks of pregnancy treated with transarterial embolization: A case report and review of the literature. (16th April 2015) - Myoen, Shingo; Mitsuzuka, Koji; Saito, Hideo; Ota, Hideki; Takase, Kei; Arai, Yoichi
Abstract Treatment for ruptured renal angiomyolipoma in pregnancy requires immediate and appropriate decision‐making based on the condition of the mother and fetus, and gestational age. A 37‐year‐old woman at 25 weeks of pregnancy presented with severe right flank pain. Computed tomography showed a ruptured right renal angiomyolipoma (8 cm in diameter). The maternal and fetal conditions were stable. Transcatheter arterial embolization was carried out electively 4 days after the rupture. Minimization of radiation exposure to the fetus was achieved by X‐ray shielding for the fetus, low‐dose‐rate fluoroscopy, minimal angiography imaging and a color Doppler ultrasonography‐guided procedure. Although threatened premature labor occurred because of post‐embolization syndrome, the pregnancy was continued until cesarean section at 37 weeks of pregnancy.